The grammar crammer : how to write perfect sentences - Kesselman-Turkel, Judi (Study smart series., 2003)
Explains some of the more troublesome and confusing aspects of English grammar under the topics of nouns, pronouns, verbs, modifiers, sentences, conjunctions and prepositions, and punctuation. Includes practice quizzes.